Mechanochemical destruction of a chlorinated polyfluorinated ether sulfonate (F-53B, a PFOS alternative) assisted by sodium persulfate1. Issue 104 (11th November 2015) - Yan, Xue; Liu, Xitao; Qi, Chengdu; Wang, Dali; Lin, Chunye
<x xml:space="preserve">Abstract</x> Persulfate (PS) can be activated by NaOH and the PS–NaOH assisted mechanochemical destruction method is effective for the degradation of F-53B.